Serum oncostatin M at baseline predicts mucosal healing in Crohn's disease patients treated with infliximab. Issue 2 (7th June 2020) - Bertani, Lorenzo; Fornai, Matteo; Fornili, Marco; Antonioli, Luca; Benvenuti, Laura; Tapete, Gherardo; Baiano Svizzero, Giovanni; Ceccarelli, Linda; Mumolo, Maria Gloria; Baglietto, Laura; de Bortoli, Nicola; Bellini, Massimo; et al.
Summary: Background: Oncostatin M is upregulated in Crohn's disease inflamed intestinal mucosa, and has been suggested as a promising biomarker to predict responsiveness to anti‐TNF therapy in patients with inflammatory bowel diseases. Aim: To evaluate the suitability of serum oncostatin M as a predictive marker of response to infliximab in Crohn's disease. Methods: We included patients treated with infliximab monotherapy. All patients underwent colonoscopy at week 54 to evaluate mucosal healing. Serum oncostatin M and faecal calprotectin were measured at baseline and after 14 weeks of treatment. Mann‐Whitney test was used to evaluate correlation of oncostatin M and faecal calprotectin at baseline and week 14 with mucosal healing at week 54. Their accuracy in predicting mucosal healing was assessed by area under the curve (AUC). Results: In a cohort of 45 included patients, 27 displayed mucosal healing. At both baseline and week 14, oncostatin M levels were significantly lower in patients with mucosal healing than in patients not achieving this endpoint ( P  < 0.001). Faecal calprotectin levels at week 14 were lower also in responders than nonresponders ( P  < 0.001). Oncostatin M values at baseline and week 14 were significantly associated (Spearman correlation = 0.92, P  < 0.001). The diagnostic accuracy of oncostatin M at baseline in predicting mucosal healing (AUC = 0.91) was greater than faecal calprotectin (AUC = 0.51, P  < 0.001). Conclusion: These results suggest that oncostatin M can predict the outcome of infliximab treatment. Compared with faecal calprotectin, the predictive capability of oncostatin M was appreciable at baseline, thus indicating oncostatin M as a promising biomarker for driving therapeutic choices in Crohn's disease.